2010
DOI: 10.1037/a0018360
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and psychological process.

Abstract: The author reviews the articles in the Special Section on Mindfulness, starting from the assumption that emotions evolved as signaling systems that need to be sensitive to environmental contingencies. Failure to switch off emotion is due to the activation of mental representations of present, past, and future that are created independently of external contingencies. Mindfulness training can be seen as one way to teach people to discriminate such "simulations" from objects and contingencies as they actually are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
127
0
18

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(148 citation statements)
references
References 39 publications
3
127
0
18
Order By: Relevance
“…Psychodynamic approaches, for example, cultivate an Bobserving self^or meta-awareness (Schooler et al 2011) to defuse automatic thinking or feeling in order to interrupt the stress response (Williams 2010). What may be unique to mindfulness training is the practice of a particular attitudinal response to awareness, as reported by our participants.…”
Section: Discussionmentioning
confidence: 76%
“…Psychodynamic approaches, for example, cultivate an Bobserving self^or meta-awareness (Schooler et al 2011) to defuse automatic thinking or feeling in order to interrupt the stress response (Williams 2010). What may be unique to mindfulness training is the practice of a particular attitudinal response to awareness, as reported by our participants.…”
Section: Discussionmentioning
confidence: 76%
“…This notion was supported in a qualitative study of MBSR participants' diary entries in a small community sample of women 30 as well as an examination of a subset (n = 13) of the cohort in the present study 31 . Equally important may be reductions in self-referential thinking, especially narrative self-reference that perpetuates negative self-judgments and dsyphoria 32 . Several studies have shown that increases in mindfulness are associated with decreases in rumination [33][34][35] and increases in mindfulness have been hypothesized to moderate outcomes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…terjadi ketika subjek memperlakukan rekonstruksi mental atas masa lalu dan masa depan sebagai ancaman nyata yang harus diatasi saat ini (Williams, 2010). Akibatnya, suatu emosi menjadi episode yang berkelanjutan tanpa kehadiran stimulus yang relevan, sementara cues lingkungan yang seharusnya diberi atensi malah menjadi terabaikan.…”
Section: Masalahunclassified
“…Emosi menjadi sinyal yang mempersiapkan subjek agar menampilkan respons sesuai tuntutan lingkungan sekaligus mengarahkan atensinya kepada cues lingkungan yang ia anggap penting (Bradley, 2009). Agar fungsi emosi menjadi efektif, kualitas yang harus dimiliki adalah (1) mengalami aktivasi ketika dibutuhkan, dan (2) mengalami deaktivasi saat situasi lingkungan berubah (Williams, 2010).…”
unclassified